Effect of the chemical nature of fixed-bed reactor support materials on bioreactor performance and biomass accumulation - B. Sen; M. Torrijos; P. Sousbie; J. P. Steyer (Global Journal of Environmental Science and Management, 2015)
This study investigated the effect, on reactor performance and biomass retention inside the bed, of the material used to make the supports of anaerobic fixed-bed reactors. Three inert supports of similar shape but made of three different materials polyvinyl chloride, polypropylene, high-density polyethylene were manufactured and used. All three supports had the same specific surface area but different relative densities. Three identical 10 L lab-scale upflow anaerobic fixed-bed reactors were filled (80% of the working volume) each respectively with polyvinyl chloride, polypropylene and polyethylene support, and fed with vinasse (44 g total COD/L) for 140 days at 35 °C. The organic loading rates were increased from 0.5 g/L.d to the maximum acceptable by each reactor. Fairly similar maximum organic loading rates were reached for each type of support, with values above 20 g of COD/L.d and more than 80 % soluble chemical oxygen demand removal efficiency. A very large amount of biomass was entrapped and attached in all the supports and represented more than 95% of the total biomass inside the reactors. In terms of performance and biomass accumulation, this study demonstrated quite similar behavior for anaerobic fixed-bed reactors with supports made of different materials, which suggests that the nature of the material used to make the supports has no major influence. The chemical nature of the support material clearly has negligible effect and thus the size, shape, and porosity of the support must be more influential.